2021
DOI: 10.51253/pafmj.v71i2.4528
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Efficacy of Intradermal Tranexamic Acid With Topical 20% Azelaic Acid in the Treatment of Melasma

Abstract: Objective: To compare the efficacy of Intradermal Tranexamic acid and topical 20% Azelaic acid cream in the treatment of melasma. Study Design: Comparative prospective study. Place and Duration of Study: Dermatology department, Combined Military Hospital Peshawar, from Sep 2018 to Mar 2019. Methodology: A total of 116 female patients, at the outpatient department of dermatology at Combined Military Hospital Peshawar, were randomly assigned into two groups; group A (intradermal tranexamic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The statistical significance of these differences, underscored by a Pvalue of 0.00, clearly favored tranexamic acid over azelaic acid in treating melasma. These observations align with previous studies, such as those by Sayyida Komal et al (19) and Fahmida Malik (20), which also reported superior outcomes with tranexamic acid, both in monotherapy and in combination with other treatments, compared to azelaic acid. Moreover, Nasrin Saki's controlled trial (21) lends further support, illustrating the rapid onset of action of intradermal tranexamic acid compared to 2% hydroquinone, albeit with comparable long-term efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…The statistical significance of these differences, underscored by a Pvalue of 0.00, clearly favored tranexamic acid over azelaic acid in treating melasma. These observations align with previous studies, such as those by Sayyida Komal et al (19) and Fahmida Malik (20), which also reported superior outcomes with tranexamic acid, both in monotherapy and in combination with other treatments, compared to azelaic acid. Moreover, Nasrin Saki's controlled trial (21) lends further support, illustrating the rapid onset of action of intradermal tranexamic acid compared to 2% hydroquinone, albeit with comparable long-term efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…Sample size was calculated to be 88 (44 females in each group) by using the hypothesis tests for two population proportions (one sided test). Intradermal Tranexamic acid in group A (P1= 31%) 13 , IPL in group 2 B (P2= 49.5%).…”
Section: Methodsmentioning
confidence: 93%
“…11 Taking level of significance 5% and Power of test 80%, using the following formula The difference in efficacy between the two groups was found to be statistically significant (p = 0.001). 13 Another study done in Egypt by Fawzy et al, sixty females received weekly sessions of intradermal tranexamic acid treatment. The decrease in mMASI score after treatment was found to be statistically significant (p value < 0.001*).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have compared the clinical effectiveness of azelaic acid in comparison to hydroquinone in skin hyperpigmentation management. Based on the reports, azelaic acid was superior to hydroquinone in terms of hyperpigmentation treatment ( Baliña and Graupe, 1991 ; Farshi, 2011a ; Komal et al, 2021 ; Sobhan et al, 2023 ). Despite the promising therapeutic potential of azelaic acid in melasma, however due to limited water solubility and poor skin permeability, its conventional topical formulations have been fabricated in higher doses (10%–20%) to achieve the desired clinical outcome ( Sieber and Hegel, 2014 ; Sobhan et al, 2023 ).…”
Section: Therapeutic Options and Limitationsmentioning
confidence: 99%